UNDERSTANDING WATER SCARCITY AND CONFLICT DYNAMICS IN AFRICA: ADDRESSING GEOPOLITICAL TENSIONS, HUMAN SECURITY, AND DEVELOPMENTAL IMPACTS - Ali MADOUNI (Humanities and Social Sciences)
This article examines the intricate relationship between water scarcity and conflict dynamics in Africa, where crucial environmental pressures intersect with escalating sociopolitical conflicts. Water shortage, resulting from climate change and population growth, leads to increased competition for limited resources and a more significant possibility for violence. Transboundary conflicts over shared water bodies, such as the Nile Basin, have often enclosed this critical confluence of contending national interests overlaid with concerns around regional stability. Securitization theory acts as a lens conceptual framework that explains how water insecurity, under a nationalizing frame, became a national security issue with prior incipient policy trends and deepening socioeconomic disparities. The document discusses the implication of water-related challenges for human security, especially in vulnerable communities that depend on agriculture and natural resources, and helps to develop informed policies that foster peace, stability, and equitable development underpinned by water scarcity in Africa through synthesizing theoretical insights and empirical findings.